2013
DOI: 10.5194/nhess-13-3281-2013
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial analyses on seismo-electric anomalies associated with the 27 February 2010 <i>M</i> = 8.8 Chile earthquake observed by DEMETER satellite

Abstract: Abstract. This paper studies seismo-electromagnetic anomalies observed by the French satellite DEMETER (Detection of Electro-Magnetic Emissions Transmitted from Earthquake Regions) during the 27 February 2010 M = 8.8 Chile earthquake. The nighttime electron density (N e ), electron temperature (T e ), ion density (N i ), ion temperature (T i ) and whistler counts (C w ) are investigated. A statistical analysis of the box-and-whisker method is applied to see if data of two or more groups under study are signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The related electromagnetic perturbations can be traced back along the magnetic field line to the region of earthquake activities [ Pulinets and Legen ' ka , ; Pulinets and Boyarchuk , ; Liu et al ., ]. These precursor phenomena include the presence of electron density fluctuations in the ionosphere above the seismic regions [ Liu et al ., ; Kakinami et al ., ; Heki , ], the change of ionic composition and temperature of plasma in the ionosphere [ He et al ., ; Oyama et al ., ; Ho et al ., ], and oscillation of the height profile of the ionospheric F region [ Afraimovich et al ., ; Astafyeva and Heki , ; Cahyadi and Heki , ].…”
Section: Introductionmentioning
confidence: 99%
“…The related electromagnetic perturbations can be traced back along the magnetic field line to the region of earthquake activities [ Pulinets and Legen ' ka , ; Pulinets and Boyarchuk , ; Liu et al ., ]. These precursor phenomena include the presence of electron density fluctuations in the ionosphere above the seismic regions [ Liu et al ., ; Kakinami et al ., ; Heki , ], the change of ionic composition and temperature of plasma in the ionosphere [ He et al ., ; Oyama et al ., ; Ho et al ., ], and oscillation of the height profile of the ionospheric F region [ Afraimovich et al ., ; Astafyeva and Heki , ; Cahyadi and Heki , ].…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement in ionospheric temperatures due to seismic activity has been reported (Sharma et al, 2013;Ho et al, 2013;Sarkar et al, 2012). However, Oyama et al, (2008) used Hinotori satellite data and observed decrease in Te during pre and post seismic events.…”
Section: Variation Of O + Ion Density During Earthquakesmentioning
confidence: 99%
“…The statistical analyses of ionospheric temperatures (Te and Ti) are comparatively less rich (Shen et al, 2015). increases as an effect of seismic activity (for example Oyama et al, 2016;Ho et al, 2013;Sarkar et al, 2012). However, these studies were conducted using DEMETER and DMSP satellite having an average altitude of 700 and 800 km respectively.…”
Section: Variation Of O + Ion Density During Earthquakesmentioning
confidence: 99%
“…After considering ionospheric variation during earlier days before the earthquake, Píša et al (2011) observed an anomalous increase of the O + ion density from DEMETER data over the epicenter area 10-20 d before the earthquake. Ho et al (2013a) further performed a cross-examination of temporal variations of electron density before and after the earthquake. The results demonstrate that the electron density increases appear 10-20 d before the earthquake.…”
Section: Other Earthquakesmentioning
confidence: 99%